The Impact of High-Stakes Testing: The Experiences of Educators, Students, and Parents in Trinidad and Tobago - Cunningham, Victoria Maria (University of Sheffield, 2021)
Students completing primary schooling in Trinidad and Tobago must pass the high-stakes Secondary Entrance Assessment (SEA) exam to be promoted. Although there are sufficient schools to accommodate students, the competition for high scores is equated and rewarded with placements into a few elite secondary schools. Failure to get a placement in a prestigious school can have a negative social, psychological, and emotional impact on students. This research describes and interprets the experiences of thirteen participants, and finds out their inherent beliefs and values and the ways their experiences impact their lives. Using a qualitative methodological design with unstructured and semi-structured in-depth interviews, data was collected from a purposive sample of 13 participants inclusive of primary school principals, teachers, students, and parents. Documentary analysis of pre-SEA students’ writings was also used to generate data. Abraham Maslow’s and Carl Roger’s humanistic theory of psychology and personality development, and Paulo Freire’s and Henry Giroux’s critical pedagogy helped me to make sense of the collected data. A critical theoretical approach was taken using thematic analysis to arrive at my findings that are presented thematically. Findings revealed experiences of fear, academic pressure, stress and test anxiety, negative feelings, and suicidal ideation. Participants had strong educational expectations, valued extra-lesson, believed in the prestige school ideology, and believed in educational inequity. Self-recrimination, play deprivation, diminished self-worth, approval-seeking, validation behaviour, a cycle of academic indoctrination, and a helicopter parenting style, were some of the ways participants were impacted. This research study is part of a growing body of knowledge and will contribute to future research on the assessment practices and behaviours that are needed to promote students’ well-being rather than focus on judging the students’ worth.
Keywords: High-stakes testing; Educators; Students; Parents; Trinidad and Tobago; Qualitative research